Non-invasive micro-test technology and applications - Sun, Kai; Liu, Yunqi; Pan, Yanshu; Di, Dongwei; Li, Jianfang; Xu, Feiyun; Li, Li; Mimata, Yoshiharu; Chen, Yingying; Xie, Lixia; Wang, Siqi; Qi, Wenqian; et al. (Biophysics reports, 2025)
Non-invasive micro-test technology (NMT) reveals dynamic ionic/molecular concentration gradients by measuring fluxes of ions and small molecules in liquid media in 1D, 2D or 3D fashions with sensitivity up to pico- (10 ) or femto- (10 ) moles per cm per second. NMT has been applied to study metabolism, signal transduction, genes and/or proteins physiological functions related to transmembrane ionic/molecular activities with live samples under normal conditions or stress. Data on ion and/or molecule homeostasis (IMH) by NMT in biomedical sciences, plant and crop sciences, environmental sciences, marine and space biology as well as traditional Chinese medicine are reviewed.